Adaptive Changes in the Vestibular System of Land Snail to a 30-Day Spaceflight and Readaptation on Return to Earth - Aseyev, Nikolay; Vinarskaya, Alia Kh.; Roshchin, Matvey; Korshunova, Tatiana A.; Malyshev, Aleksey Yu.; Zuzina, Alena B.; Ierusalimsky, Victor N.; Lemak, Maria S.; Zakharov, Igor S.; Novikov, Ivan A.; Kolosov, Peter; Chesnokova, Ekaterina; et al. (Frontiers in Cellular Neuroscience, 2017)
The vestibular system receives a permanent influence from gravity and reflexively controls equilibrium. If we assume gravity has remained constant during the species’ evolution, will its sensory system adapt to abrupt loss of that force? We address this question in the land snail Helix lucorum exposed to 30 days of near weightlessness aboard the Bion-M1 satellite, and studied geotactic behavior of postflight snails, differential gene expressions in statocyst transcriptome, and electrophysiological responses of mechanoreceptors to applied tilts. Each approach revealed plastic changes in the snail’s vestibular system assumed in response to spaceflight. Absence of light during the mission also affected statocyst physiology, as revealed by comparison to dark-conditioned control groups. Readaptation to normal tilt responses occurred at ~20 hr following return to Earth. Despite the permanence of gravity, the snail responded in a compensatory manner to its loss and readapted once gravity was restored.